Management of tibial bone defect in Malaysian public hospital - Mohd Yusof, Nazri; Sulong, Ahmad Fadzli (2015)
Introduction Management of segmental tibial defect depends not only on clinical ground but also the acceptance and patients social circumstances . The incidence of pin site infection is higher during high temperature season. In our center, autologous bone grafting stabilized with plate osteosynthesis is the preferred method of managing tibial defect while ilizarov bone transport is use when the size of defect is large or poor condition of the soft tissue. Objective The aim of this study is to evaluate the clinical outcomes in patients undergoing reconstruction of tibial bone defect using Ilizarov bone transport and plating with autologous bone graft. Methods The study was done in the Department of Orthopaedic, Hospital Tengku Ampuan Afzan Kuantan, Pahang, Malaysia from 2007 till 2014. There were 29 patients with the mean age of 27.5 years old (range 13-64). The aetiology were from infected open fracture 20 cases, grade IIIB open fracture in 2 cases, grade IIIA with bone loss in one case, infection after interlocking nail in 3 cases, infection after plating in one cases and atropic non union in 2 cases. Sixteen patients underwent ilizarov bone transport and 13 patients underwent plating and bone graft. Twenty one patients also have wound defect with a mean size of 13.9 cm2 (range 4 to 28). Results and discussions Twenty six patients achieve union with a mean union time of 9.3 months (range 4-20 months). The mean size of bone defect for the bone transport group was 4.4 cm (range 2 to 10 cm).The mean union time for patient underwent bone transport was 10.8 months (range 5 to 20 months). The mean size of bone defect for the plating and bone graft group was 2.5 cm (range 2-4 cm). The mean union time was 6.4 months (range from 4 to 7 months). Three patients with plating and bone graft group had recurrence of infection following the procedure. None of the patients in the ilizarov group has recurrence of infection. Three patients failed to unite , one from the ilizarov group and 2 from the plating and bone graft group. The ilizarov group have problems related soft tissue like joint stiffness and contracture. Whereas the bone graft group had problems with recurrence of infection and broken implant. Conclusion Knowing the procedure complication and educating our patients are important to achieve best clinical outcome in our center.